2004
DOI: 10.1203/01.pdr.0000113463.70435.74
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Epithelial Apoptosis Initiates Gross Bowel Necrosis in an Experimental Rat Model of Neonatal Necrotizing Enterocolitis

Abstract: The histopathology of necrotizing enterocolitis (NEC) is characterized by destruction of the mucosal layer in initial stages and by transmural necrosis of the intestinal wall in advanced stages of the disease. To test the hypothesis that enhanced epithelial apoptosis is an initial event underlying the gross histologic changes, we analyzed epithelial apoptosis and tissue morphology in an animal model of NEC and evaluated the effect of caspase inhibition on the incidence of experimental NEC in this model. Apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
165
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(184 citation statements)
references
References 45 publications
10
165
0
1
Order By: Relevance
“…In the physiological process of intestinal mucosa renewal, in addition to cell proliferation, the process of apoptosis of epithelial cells also occurs 22 . Jilling et al 22 evaluated apoptosis in Neonatal necrotizing enterocolitis rat model attenuated by a remote ischemic preconditioning in the pregnant Gomes ROL et al Acta Cir Bras.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the physiological process of intestinal mucosa renewal, in addition to cell proliferation, the process of apoptosis of epithelial cells also occurs 22 . Jilling et al 22 evaluated apoptosis in Neonatal necrotizing enterocolitis rat model attenuated by a remote ischemic preconditioning in the pregnant Gomes ROL et al Acta Cir Bras.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Jilling et al 22 evaluated apoptosis in Neonatal necrotizing enterocolitis rat model attenuated by a remote ischemic preconditioning in the pregnant Gomes ROL et al Acta Cir Bras. 2017;32(3):236-242 241 the gut of newborn rats, demonstrating that it was already present at a time prior to the onset of necrosis and that the frequency of apoptosis was lower in animals with higher injury degree of the intestinal mucosa.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study we have found that heterologous over-expression of Bcl-2, a molecular antagonist of Bax, prevented PAF-induced collapse of mitochondrial membrane potential and apoptosis in these cells, indicating that mitochondrial damage is important in the mechanism of PAF-induced apoptosis, and suggesting that understanding the expression profiles of the Bcl family of apoptosis regulators during intestinal development may be important for our understanding of NEC pathogenesis. In light of our earlier observation that wide-spread enterocyte apoptosis precedes and accompanies gross tissue necrosis in an animal model of NEC and that caspase inhibition prevents the development of experimental NEC [76], our in vitro evidence for PAF-induced enterocyte apoptosis is a significant observation to aid our mechanistic understanding of NEC pathogenesis. Additionally, we have shown that PAF does not only directly regulate apoptosis, but that signaling via the PAFR induces TLR4 expression in enterocytes (unpublished data).…”
Section: Pro-apoptotic Signaling In Necmentioning
confidence: 62%
“…Investigation of human intestinal samples that was obtained during surgery for NEC revealed that there is an abundance of apoptotic nuclei in the epithelium of intestines affected by NEC [75]. To determine whether this observation is a mere coincidence, or whether apoptosis may indeed play a pathological role in NEC, we investigated [76]. Since this early observation, several studies have shown that the development of experimental NEC is halted by various growth factors that cause enterocyte cell survival, such as EGF [77], IGF-I [78] and hb-EGF [79], or by a blocking antibody to TNFα [80] which is a proapoptotic molecule for enterocytes in vitro [81].…”
Section: Enterocyte Apoptosis In Necmentioning
confidence: 99%